Finding Home in a Hopeless Place: Schools as Sites of Heteronormativity. Issue 1 (3rd April 2023) - Cohen, Sarah Simi; Duarte, Bryan J.; Ross, Jennifer
ABSTRACT: For this study, we operated with a critical theoretical understanding of schools as sites of (cis)heteronormativity, which led us to question the impact of heteronormative schooling environments. We used data from the 2017 national Youth Risk Behavior Surveillance System to examine the self-reported experiences and feelings of high school students with gay or lesbian, bisexual, or questioning identities. Additionally, we used a quantitative intersectional approach to juxtapose the lived experiences of queer youth in the data with our own counternarratives. Our findings indicate that queer students experienced sadness and/or hopelessness, which was predicted by unsafe schooling experiences and signs of mental health trauma and exacerbated by intersecting marginal identities (i.e., race, ethnicity, gender). Our counternarratives suggest that LGBTQIAA+ youth may experience dissonance among their sense of belonging, home, and identity that is caused by the oppressive cis-heteronormative structures of their schooling systems, which may negatively impact their mental health. Although this dissonance is ever-present, we argue that queer and trans students resist these cis-heteronormative structures through homing, which allows these students to create a more equitable environment for themselves and others.